A cobalt coordination compound with indole acetic acid for fabrication of a high performance cathode catalyst in fuel cells. Issue 23 (17th February 2016) - Liu, Bin Hong; Dou, Li Ting; He, Fan; Yang, Jun; Li, Zhou Peng
Abstract : Construction of coupling site with electrophilic and nucleophilic centers is the key to enhance ORR in acidic electrolyte. Abstract : As a catalyst precursor, a cobalt coordination compound with indole acetic acid (Co–IAA) was synthesized using the hydrothermal method. Pyrolysis significantly improved the catalytic activity of the carbon supported Co–IAA (Co–IAA/BP) toward the oxygen reduction reaction (ORR) due to the formation of nano-Co3 O4 . Both original and pyrolyzed Co–IAA/BP exhibited higher catalytic activity in an alkaline electrolyte than that in an acidic one because dioxygen and water were absorbed at the single electrophilic Co center in the alkaline electrolyte but dioxygen and proton were separately absorbed at the electrophilic Co center and nucleophilic center (O) in the acidic electrolyte. Construction of a coupling site where electrophilic and nucleophilic centers coexisted was the key to enhance the ORR in an acidic electrolyte. The pyrolyzed Co–IAA/BP exhibited excellent performance in the direct borohydride fuel cell, comparable to the commercialized 20 wt% Pt/XC-72. A peak power density as high as 186 mW cm −2 was achieved at ambient conditions.